Factors Influencing the Formation of Autopoietic Economic Structures in the Baltic States - Mangirdas Morkunas; Viktorija Skvarciany; Jelena Titko (Institute of Economic Research (IER), 2017)
The concept of autopoiesis was initially developed in the field of biology and it was used to explain the behavior of biological systems. However it has been successfully applied in other fields of science, including economics and management. Although researches on economic entities using autopoietic systems' theory are performed in Western Europe and USA, this scientific approach still is not developed in Baltic countries. This paper addresses to this vacuum of scientific researches on autopoiesis of economic structures in small open markets. The paper aims to identify and evaluate factors that turn on self-organization mechanisms of autopoietic economic structures in Baltic States, in particular in Latvia. Expert survey was used to identify the most important factors affecting the formation of meso-economic entities in the Baltic States. Analytic Hierarchy Process (AHP) with fuzzy numbers was employed to process the data. Two different scales of evaluation (inverse linear and balanced) were used. The factors influencing the process of formation of business groups were evaluated by experts. Research results allow making conclusions regarding the causes of the business integration, and impact of diversified integrated business structures on the country's business system in Central Europe.
Keywords: D21; L22; 330; autopoiesis; formation of a firm; Baltic States